Emotional level among psychiatric nurses in Kuala Lumpur and Selangor Hospital / Nabilah Hasdi…[et al.] - Hasdi, Nabilah; Wan Jaffar, Wan Nur Akmal; Wan Hassan Beshari, Wan Siti Zakirah (2015)
BACKGROUND: Nurses had a close relationship with patients compared to other professions in the hospital especially psychiatric nurses who needed to deal with behavioral problems of patients such as self murder, assaults, cruelty and turbulence. Long time exposure to these stressors could lead nurses to become stress and depressed (Mi et al, 2015). Stressful conditions among nurses were identified to be the factors of absenteeism, turnover, lower hospital responsibilities and lower job contentment (Atindanbila et al., 2012). The purpose of study was to determine the emotional level (stress, anxiety and depression) among psychiatric nurses in Kuala Lumpur and Selangor Hospital. METHODS: Quantitative study with descriptive and inferential statistical approaches using self-reported questionnaires (DASS-21) was conducted involving 85 psychiatric nurses in Hospital Kuala Lumpur, Hospital Tengku Ampuan Rahimah and Hospital Selayang. The method used was purposive sampling. RESULTS: Total respondents were 85, most of the respondents were Malay (n=80, 94.1%), married (n=59, 69.4%) female psychiatric nurses (n=72, 84.7%) who worked in psychiatric ward (n=52, 61.2%). Mean age of the respondents was 29.60 (SD: 6.253). Most of the participants had tertiary educational level (n: 61, 71.8%) with minimum year of service less than one year and maximum year of service 30 years in service. 87.1% of the respondents were in grade U29 and 84.7% were working in morning shift during answering this research questionnaire. In this study, more than half of the participants never had double shift for past one month (n=44, 51.8%) and mean economic status was RM2167.91 (SD: 801.47). Most of psychiatric nurses had normal level of stress (n=74, 87.1%), anxiety (n=52, 61.2%) and depression (n=70, 82.4%). There were significant difference between depression with age (pvalue: 0.009) and educational level (p-value: 0.021). There were also significant difference between level of stress and age (p-value: 0.005), and between level of anxiety with age (pvalue: 0.002). CONCLUSIONS: There was significant difference between emotional level with age and level of depression with educational level. Therefore, psychiatric nurses need to learn on how to control their emotions when dealing with the patients5 mental health problems.